A casa da atriz: uma cartografia desassossegada das sociabilidades de um coletivo teatral em Belém do Pará - PORTO, Luciana de Andrade Moreira (Universidade Federal do Pará, 2018)
The House of Actress: A Cartography of Disquieted Sociability’s a Theatrical Collective in Belem takes over as creative principle risk up by forked paths, the investigation of daily negotiations this theater collective demands. The researcher knows for breaking initial ways of mapping must create an existential territory between the previous days and the present, to understand the need or not, the existence of home-womb. Its background research, other houses headquarters here recognized as interior geographies where locals and shelters are confused, converging memories, feelings and poetic. As an object, existing dichotomous feelings and residents in both structures (traveler and home). In the midst of the paths in between, the choice of the researcher is to be cartographer of the soul and unrest, walker and resident. When launching the path of poetic thought, discovers the traces of steps left in the boiling asphalt other foot, then it is known accompanied by other hikers in books: Gaston Bachelard saying the most precious, the have and being home; Fernando Pessoa poeticizing that existing restless wanderings in the plans of ideas and life are but a power test turn out to be; Lewis Carroll and Alice as beings who risk the new, all the time; Hilda Hist burning desires and Ítalo Calvino, in this imaginary lines, which depicts and recognizes through the fable, the habitat itself. Assuming the error and the unfinished as part of the paths taken, it precipitates a new journey.